Development of a Hyperosmotic Stress Inducible Gene Expression System by Engineering the MtrA/MtrB-Dependent NCgl1418 Promoter in Corynebacterium glutamicum - Huang, Jingwen; Chen, Jiuzhou; Wang, Yu; Shi, Tuo; Ni, Xiaomeng; Pu, Wei; Liu, Jiao; Zhou, Yingyu; Cai, Ningyun; Han, Shuangyan; Zheng, Ping; Sun, Jibin (Frontiers in Microbiology, 2021)
Corynebacterium glutamicum is an important workhorse for industrial production of diversiform bioproducts. Precise regulation of gene expression is crucial for metabolic balance and enhancing production of target molecules. Auto-inducible promoters, which can be activated without expensive inducers, are ideal regulatory tools for industrial-scale application. However, few auto-inducible promoters have been identified and applied in C. glutamicum. Here, a hyperosmotic stress inducible gene expression system was developed and used for metabolic engineering of C. glutamicum. The promoter of NCgl1418 (PNCgl1418) that was activated by the two-component signal transduction system MtrA/MtrB was found to exhibit a high inducibility under hyperosmotic stress conditions. A synthetic promoter library was then constructed by randomizing the flanking and space regions of PNCgl1418, and mutant promoters exhibiting high strength were isolated via fluorescence activated cell sorting-based high-throughput screening. The hyperosmotic stress inducible gene expression system was applied to regulate the expression of lysE encoding a lysine exporter and repress four genes involved in lysine biosynthesis (gltA, pck, pgi, and hom) by CRISPR interference, which increased the lysine titer by 64.7% (from 17.0 g/L to 28.0 g/L) in bioreactors. The hyperosmotic stress inducible gene expression system developed here is a simple and effective tool for gene auto-regulation in C. glutamicum and holds promise for metabolic engineering of C. glutamicum to produce valuable chemicals and fuels.